(untitled) (Journal of Economic Research & Business Administration, 2015)
The article deals with the nature of relations between the center and territories, as well as the distribution of powers between them. As a positive example in this regard, presented experience of the European Union. It is shown that despite the positive dynamics of economic growth, there is a sharp differentiation in development among the regions of Kazakhstan. It has been concluded, that the problem of "regionalization" of state regulation of economic development rises in the economic agenda as one of the most acute, is complex and requires an urgent solution because a slowdown in its decision can cause serious contradictions within realization of concept of opposition to the new economic crisis.